Agreement Technologies - Ossowski, Sascha (Law, Governance and Technology Series, 2013)
More and more transactions, whether in business or related to leisure activities, are mediated automatically by computers and computer networks, and this trend is having a significant impact on the conception and design of new computer applications. The next generation of these applications will be based on software agents to which increasingly complex tasks can be delegated, and which interact with each other in sophisticated ways so as to forge agreements in the interest of their human users. The wide variety of technologies supporting this vision is the subject of this volume. It summarises the European Cooperation in Science and Technology (COST) Action project on Agreement Technologies (AT), during which approximately 200 researchers from 25 European countries, along with eight institutions from non-COST countries, cooperated as part of a number of working groups. The book is the first to provide a comprehensive overview of the emerging field of Agreement Technologies, written and coordinated by the leading researchers in the field. The results set out here are due for wide dissemination beyond the computer technology sector, involving law and social science as well.